Rapid effect of inhaled fluticasone propionate on airway responsiveness to adenosine 5′-monophosphate in mild asthma - Ketchell, Robert I.; Jensen, Marianne W.; Lumley, Philip; Wright, Andrew M.; Allenby, Mark I.; O'Connor, Brian J. (Journal of allergy and clinical immunology, 2002)
Inhaled adenosine 5′-monophosphate (AMP) has an “indirect” bronchoconstrictive effect through mast cell degranulation and mediator release, whereas inhaled histamine has a “direct” effect on smooth muscle. Prolonged treatment with inhaled glucocorticosteroids attenuates airway responsiveness (AR) to AMP and histamine. We investigated the early effects of inhaled fluticasone propionate (FP) therapy on AR in 3 consecutive double-blind, randomized, placebo-controlled crossover studies in steroid-naive subjects with mild asthma. In one study, each of 12 subjects received FP 1000 μg or matched placebo for 7 inhalations at 12 hourly intervals; AR to AMP and FEV1 were measured 2 hours after the 3rd and 7th inhalations. In a second study, each of 12 subjects received FP 100, 250, or 1000 μg or matched placebo for 3 inhalations at 12 hourly intervals; AR to AMP and FEV1 were measured 2 hours after the 1st and 3rd inhalations. In a third study, each of 8 subjects received a single inhalation of FP 1000 μg or matched placebo; AR to histamine was measured 2 hours later. In the first study, FP 1000 μg significantly attenuated AR to AMP by 2.7 and 2.5 doubling doses after 3 and 7 inhalations, respectively (P ≤ .0001). In the second study, FP 100, 250, and 1000 μg significantly attenuated AR to AMP by 1.9, 2.2, and 2.7 doubling doses, respectively, after 1 inhalation and by 2.4, 2.2, and 3.2 doubling doses, respectively, after 3 inhalations (P ≤ .0001); a small but significant increase in FEV1 (>0.15 L) was observed after 3 inhalations but not after 1 inhalation of FP irrespective of dose (P ≤ .05). In the third study, a single inhalation of FP 1000 μg had no effect on AR to histamine. We have demonstrated a reduction in AR to AMP but not AR to histamine within 2 hours of a single inhalation of FP. This reflects a rapid, topical anti-inflammatory action of inhaled FP by a mechanism of action that remains unknown. (J Allergy Clin Immunol 2002;110:603-6.)